Synergistic Effect of a Physiological Ratio of Estradiol and Testosterone in the Treatment of Early-stage Atherosclerosis - Dai, Wen; Ming, Wang; Li, Yan; Zheng, Hong-yun; Wei, Chuan-dong; Rui, Zhao; Yan, Cui (Archives of medical research, 2015)
Clinical trials and epidemiological data suggest that estrogen replacement therapy (ERT) fails to reduce cardiovascular events in postmenopausal women with coronary heart disease (CHD). The high concentration of estrogen supplementation may increase the risk of thrombosis and result in testosterone deficiency, which is considered the main reason for failure. Thus, we hypothesized that a physiologic dosage of estradiol combined with testosterone may become a new therapeutic strategy in postmenopausal women with CHD. We used human umbilical vein endothelial cells (HUVECs) and female C57BL/6 mice as the experimental subjects. With the HUVECs, we found an appropriate E2/T ratio of 5:1 (5×10−8 mol/L estradiol and 10−8 mol/L testosterone), which has a significant anti-apoptotic effect on HUVECs by inducing a C-reactive protein. In the in vivo study, we verified the beneficial effects of the defined appropriate E2/T ratio in mice with early stage atherosclerosis. We found that replacement therapy with the defined appropriate E2/T ratio had beneficial effects of reducing the lipid lesions, reducing the formation of foam cells, reducing endothelial injury, modulating the coagulation system function and inhibiting inflammation and was significantly more effective than either estradiol or testosterone supplementation alone. The present study demonstrated that estradiol and testosterone have a synergistic effect on early stage atherosclerosis, and replacement therapy with the defined appropriate E2/T ratio can significantly suppress the development of atherosclerosis through reducing the lipid lesions, reducing the formation of foam cells, reducing endothelial injury, modulating the coagulation system function and inhibiting inflammation.